2019
DOI: 10.5213/inj.19381534.077
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of a New Smart Healthcare System: A Wearable Device-Based Complex Structure of Position Detecting and Location Recognition System

Abstract: Smart healthcare is the integration of high technology-such as artificial intelligence (AI), big data, Internet of Things (IoT), cloud, and Nano technology-with medical healthcare. Such integration can provide customized healthcare services without time and space limitations [1]. It is encouraging to look at a series of smart healthcare related studies-such as Dakurah et al. [2], Lee et al. [3], Kang et al. [4], and Myung et al. [5]-published in the International Neurourology Journal (INJ), a rising journal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Moreover, the possibility of a smart band with a recognition system was tested in a previous pilot study ( Chung et al, 2019 ). Based on these previous studies, a smart band for real users was developed, and the accuracy of this technology was tested in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the possibility of a smart band with a recognition system was tested in a previous pilot study ( Chung et al, 2019 ). Based on these previous studies, a smart band for real users was developed, and the accuracy of this technology was tested in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The data from the Arduino into the cloud gets loaded with the help of Wi-Fi module and Ethernet shield on the transport layer. However, because an Arduino Uno was utilized, several sensors were unable to be appropriately processed [ 19 ]. To track smart houses and heartbeats, a wireless sensor network (WSN) was created.…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies using a mobile app for writing sleep diaries. Although studies such as theirs have identified the need to use technologies such as mobile apps for the efficient and reliable collection of data, current sensor-based studies for analyzing sleep quality focus on self-awareness of sleep activity and the amount of activity during the day rather than on lifestyle [27]- [29]. The efficient and secure method for EMA can achieve immediate awareness of responses, as well as monitoring compliance daily.…”
Section: B Sleep Quality Prediction Using Mobile Devicesmentioning
confidence: 99%